Usability Evaluation and Recommendations for Improving the Geospasial Information System in Supporting the One Map Policy in Indonesia - Singgih Dwi Saputro; Harry Budi Santoso (AI Society & STMIK Indonesia, 2025)
The One Map Policy (OMP) is the government's strategic direction in fulfilling one map that refers to one geospatial reference in Indonesia. As a decision supporter for resolving land use discrepancies, the Information System for Indicative Maps of Overlapping Thematic Geospatial Information (SIPITTI) can accelerate the implementation of the OMP. This research aims to evaluate the usability of SIPITTI to support the resolution of overlapping land use in OMP and then design improvements to SIPITTI. This research was conducted using mixed methods, where quantitative data collection was carried out through questionnaires using the Post-Study System Usability Questionnaire (PSSUQ) and System Usability Scale (SUS). The qualitative data collection was done through usability testing. Nine respondents to the questionnaire and usability testing were involved in collecting initial needs data, which became input for the design. The results of the data analysis obtained a design that applied the principles of Shneiderman's Eight Golden Rules of Interface Design. Prototype improvements were evaluated through two techniques: usability testing and questionnaires:PSSUQ and SUS. The evaluation results using PSSUQ obtained an average value above the standard, namely overall (2.22), system usefulness (2.13), information quality (2.31), and interface quality (2.11). The SUS evaluation results amounted to 74; the value is included in the B- or Good category.